Pengaruh Dosis Pupuk Kandang Sapi terhadap Beberapa Parameter Agronomi dan Produksi Rumput Odot - Qohar, Adi Fathul; Utami, Erfilia Tri Wahyu; Fadilah, Masngud; Soleh, Ibnu (Jurnal Kridatama Sains dan Teknologi, 2022)
Odot grass (Pennisetum purpureum cv. Mott) is a perennial forage plant that is responsive to fertilization. The research was carried out from October 1 to November 30 2022 in the Grass Garden, Dukuh Sumur Kidul, Ambalkumolo Village, Buluspesantren District, Kebumen Regency. The aim of this study was to examine the effect of cow manure on several agronomic parameters and odot grass production. The research method used is experimental. The study used a completely randomized design (CRD) with 4 doses namely K0 = 0 ton/ha; K1 = 5 tonnes/ha; K2 = 10 tonnes/ha; K3 = 15 tons/ha repeated 5 times. Agronomic parameters include plant height, number of leaves, while production includes fresh production and dry matter. The results showed that the treatment had a significant effect (P<0,05) on plant height, number of leaves, fresh production and dry matter production of odot grass. The average plant height is 90,26-123,29 cm, the number of leaves is 27,16-35,27 per clump, fresh production is 3,91 – 6,19 kg per unit, dry matter production is 0,30-0.,55 kg per unit. The best dose of manure as measured from agronomic and production parameters is 15 tonnes/ha. Keywords: Agronomy, Production, Odot Grass, Manure